2017
DOI: 10.1186/s12879-017-2777-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of serological diagnosis of hepatitis C and B using dried blood spot samples (DBS): two systematic reviews and meta-analyses

Abstract: BackgroundDried blood spots (DBS) are a convenient tool to enable diagnostic testing for viral diseases due to transport, handling and logistical advantages over conventional venous blood sampling. A better understanding of the performance of serological testing for hepatitis C (HCV) and hepatitis B virus (HBV) from DBS is important to enable more widespread use of this sampling approach in resource limited settings, and to inform the 2017 World Health Organization (WHO) guidance on testing for HBV/HCV.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 57 publications
8
77
0
Order By: Relevance
“…In particular, compared with the 2004 prevalence survey based on venous blood sampling, the use of DBS in BaroTest may have led to a slight underestimation of CHC and CHB prevalences due to a possible lack of sensitivity. However, several studies, including metaanalyses, have shown excellent diagnostic accuracy (with both specificity and sensitivity higher than 98%) using DBS compared with venous blood sampling for the detection of anti-HCV antibodies, HBs Ag and HCV RNA (33)(34)(35). Although not significant, the observed decrease in CHC prevalence in the general population in metropolitan France may be linked to the decrease in the number of people infected by blood transfusion before 1992, the availability of DAAs, and the almost certain reduction in HCV incidence.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, compared with the 2004 prevalence survey based on venous blood sampling, the use of DBS in BaroTest may have led to a slight underestimation of CHC and CHB prevalences due to a possible lack of sensitivity. However, several studies, including metaanalyses, have shown excellent diagnostic accuracy (with both specificity and sensitivity higher than 98%) using DBS compared with venous blood sampling for the detection of anti-HCV antibodies, HBs Ag and HCV RNA (33)(34)(35). Although not significant, the observed decrease in CHC prevalence in the general population in metropolitan France may be linked to the decrease in the number of people infected by blood transfusion before 1992, the availability of DAAs, and the almost certain reduction in HCV incidence.…”
Section: Discussionmentioning
confidence: 99%
“…HBsAg laboratory tests have a sensitivity <0.1 IU/mL (Tuaillon et al, 2012), suggesting that even with a dilution factor of 10 or 20 times related to the elution step, the DBS testing may have a better sensitivity than HBsAg RDT. Systematic reviews have reported 98% sensitivity and 100% specificity for HBsAg screening on DBS compared to 88.9% sensitivity and 98.4% specificity using HBsAg RDT Lange et al, 2017a). By contrast, the overall performances of RDT and DBS test dedicated to anti-HCV detection appeared very close, with 98% sensitivity, and 99% specificity using DBS, and 98% sensitivity and 100% sensitivity using RDT (Lange et al, 2017a;Tang et al, 2017).…”
Section: Dbs For Screening and Serologic Confirmation Of Hiv And Viramentioning
confidence: 99%
“…Systematic reviews have reported 98% sensitivity and 100% specificity for HBsAg screening on DBS compared to 88.9% sensitivity and 98.4% specificity using HBsAg RDT Lange et al, 2017a). By contrast, the overall performances of RDT and DBS test dedicated to anti-HCV detection appeared very close, with 98% sensitivity, and 99% specificity using DBS, and 98% sensitivity and 100% sensitivity using RDT (Lange et al, 2017a;Tang et al, 2017).…”
Section: Dbs For Screening and Serologic Confirmation Of Hiv And Viramentioning
confidence: 99%
“…Once in the laboratory, the serum is eluted off the card and can be run using the standard automated serum detection systems. The first spot is tested for Ab, and if positive, the next spot is tested for HCV RNA . Because of the lower quantity of blood, the HCV RNA loads from DBS are lower than in a serum tube from the same patient by ~2 log IU/mL .…”
Section: Dried Blood Spot Testingmentioning
confidence: 99%